2014
DOI: 10.1002/cmdc.201300547
|View full text |Cite
|
Sign up to set email alerts
|

GluN2B‐Selective N‐Methyl‐d‐aspartate (NMDA) Receptor Antagonists Derived from 3‐Benzazepines: Synthesis and Pharmacological Evaluation of Benzo[7]annulen‐7‐amines

Abstract: Given their high neuroprotective potential, ligands that block GluN2B-containing N-methyl-D-aspartate (NMDA) receptors by interacting with the ifenprodil binding site located on the GluN2B subunit are of great interest for the treatment of various neuronal disorders. In this study, a novel class of GluN2B-selective NMDA receptor antagonists with the benzo[7]annulene scaffold was prepared and pharmacologically evaluated. The key intermediate, N-(2-methoxy-5-oxo-6,7,8,9-tetrahydro-5H-benzo[7]annulen-7-yl)acetami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Previous studies have shown that ap henylpropylamino group at 7-position is responsible for high GluN2B affinity. [20] To analyze the effects of various substituents at the 2-position, the phenylpropylamino moiety at the 7-position was kept almost un- Figure 2. Conformational restriction approach,starting from 2 to obtain benzo [7]annulen-7-amines 5c-7c.…”
Section: Glun2b Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that ap henylpropylamino group at 7-position is responsible for high GluN2B affinity. [20] To analyze the effects of various substituents at the 2-position, the phenylpropylamino moiety at the 7-position was kept almost un- Figure 2. Conformational restriction approach,starting from 2 to obtain benzo [7]annulen-7-amines 5c-7c.…”
Section: Glun2b Affinitymentioning
confidence: 99%
“…5c [20] OCH 3 3-10 6c [21] H3-16 AE 40% 150 27 AE 12 7a [22] NO 2 1-7.6 AE 0.7 6% 21 AE 616 AE 2 7b [22] NO 2 2-3.3 AE 1.0 8% 20 AE 544 AE 25 7c [22] NO 2 3-1.6 AE 0.9 3% 18 AE 511 AE 4 7d [22] NO 2 other bindings ite at the same target protein. In ac ompetition assay with the radioligand [ 3 H](+)-MK-801 [24,25] the synthesized benzo [7]annulen-7-amines did not show any interaction with the PCP binding site.…”
Section: Receptor Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…By a conformational restriction approach on the prototypical ligand ifenprodil ( 1 ), we obtained tetrahydro‐3‐benzazepines (including the recently reported [ 11 C]Me‐NB1 [ 11 C] 2 ) as well as benzo[7]annulen‐7‐amines ( 4 ) derived from Ro 25‐6981 ( 3 ) in a similar manner (Figure ) . Ligands of both compound classes possess high binding affinity towards the GluN2B subunit …”
Section: Introductionmentioning
confidence: 84%
“…20 Stimulated by the high GluN2B affinity of 5, the pharmacological properties of various benzo [7]annulenamines 6 without a benzylic OH-moiety should be investigated. 21 Moreover, in the first series of ligands 6 the methoxy group in 2-position of 4 and 5 should be removed to analyze the contribution of this substituent to the GluN2B affinity and selectivity.…”
Section: Introductionmentioning
confidence: 99%